Pembuatan Aplikasi Penerimaan Peserta Didik Baru Berbasis Website : Studi Kasus SMK Banjar Asri - Sani Sopian; Mamok Andri Senubekti (Jurnal Penelitian Multidisiplin Ilmu, 2023)
The process of admitting new students through the creation of an information technology-based website at SMK BANJAR ASRI. The goal is to increase the efficiency and effectiveness of new student admissions by utilizing information technology. Designing and developing a new student admission website with the features provided can increase efficiency and positive responses from prospective students and parents to the experience of using this website.The implementation of this website provides benefits in an easier, faster, and more efficient registration process for prospective students and parents. Schools also benefit from more efficient data processing and more organized monitoring.This report can be a reference for SMK BANJAR ASRI and other educational institutions that want to improve the efficiency and effectiveness of new student admissions through information technology.